Temporal Binding, Causation, and Agency: Developing a New Theoretical Framework. Issue 5 (18th May 2020) - Hoerl, Christoph; Lorimer, Sara; McCormack, Teresa; Lagnado, David A.; Blakey, Emma; Tecwyn, Emma C.; Buehner, Marc J.
Abstract: In temporal binding, the temporal interval between one event and another, occurring some time later, is subjectively compressed. We discuss two ways in which temporal binding has been conceptualized. In studies showing temporal binding between a voluntary action and its causal consequences, such binding is typically interpreted as providing a measure of an implicit or pre‐reflective "sense of agency." However, temporal binding has also been observed in contexts not involving voluntary action, but only the passive observation of a cause–effect sequence. In those contexts, it has been interpreted as a top‐down effect on perception reflecting a belief in causality. These two views need not be in conflict with one another, if one thinks of them as concerning two separate mechanisms through which temporal binding can occur. In this paper, we explore an alternative possibility: that there is a unitary way of explaining temporal binding both within and outside the context of voluntary action as a top‐down effect on perception reflecting a belief in causality. Any such explanation needs to account for ways in which agency, and factors connected with agency, has been shown to affect the strength of temporal binding. We show that principles of causal inference and causal selection already familiar from the literature on causal learning have the potential to explain why the strength of people's causal beliefs can be affected by the extent to which they are themselves actively involved in bringing about events, thus in turn affecting binding.